2018
DOI: 10.1016/j.dyepig.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of lucidin: New insights into the fate of this natural pigment present in Dyer's madder ( Rubia tinctorum L.) during the extraction of textile artefacts

Abstract: The complex mixtures of colorants present in different madder species can provide significant information about which plant species or technique was used to dye the fibres of historical textile artefacts, hence, when extracting and analysing colorants from textile artefacts as much of this information as possible should be preserved. Historical textiles are most commonly extracted with 37% hydrochloric acid: methanol: water (2:1:1, v/v/v), but this solvent system hydrolyses dye glycosides and may also induce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, minor anthraquinones reported by Armitage et al were not observed in the extract even with selected ion monitoring; namely, 1-methoxy-2-methylanthraquinone (m/z 251), 2-methoxy-2-methylanthraquinone (m/z 237), and the primeverosides of xanthopurpurin (m/z 533), rubiadin (m/z 547), and pseudopurpurin (m/z 593) [11]. Lucidin was also not detected, but its glycoside, lucidin primeveroside was observed due to the mild extraction procedure [59].…”
Section: Dye Analysismentioning
confidence: 99%
“…However, minor anthraquinones reported by Armitage et al were not observed in the extract even with selected ion monitoring; namely, 1-methoxy-2-methylanthraquinone (m/z 251), 2-methoxy-2-methylanthraquinone (m/z 237), and the primeverosides of xanthopurpurin (m/z 533), rubiadin (m/z 547), and pseudopurpurin (m/z 593) [11]. Lucidin was also not detected, but its glycoside, lucidin primeveroside was observed due to the mild extraction procedure [59].…”
Section: Dye Analysismentioning
confidence: 99%
“…The extractants used for the separation of biologically active substances from the roots of Rubia tinctorum L. include ethanol, water and their combination at various ratios [12,28]. The most common procedure described for extracting anthraquinone derivatives from Rubia tinctorum L. roots and rhizomes is performed with the 37% hydrochloric acid/methanol/water (2:1:1, v/v/v) mixture [30]. But the presence of water in extractant solutions leads to the degradation of the primary anthraquinone derivatives such as RA [12], which makes analyzing the primary anthraquinone derivatives impossible.…”
Section: Solvent Selectionmentioning
confidence: 99%
“…Those reactions may also affect the dyeing potential, as the products of hydrolysis, i.e., aglycone structures, differ in their properties and affinities to various materials compared to their derivatives [9,13]. The historical background does not necessarily give any guarantee of safeness as even widely-used dye sources can contain toxic secondary metabolites: madder root extracts (R. tinctorum) having alizarin (1) as the main anthraquinone aglycone, also contained toxic lucidin (2), rubiadin (3) and xanthopurpurin (4) (Table 1) [26][27][28][29][30], of which lucidin and xanthopurpurin were hydrolysis and decarboxylation products of lucidin primeveroside and munjistin. Furthermore, it has been proposed that lucidin is converted into other compounds, such as nordamnacanthal or quinone methide [26,28,31] or degrade to xanthopurpurin.…”
Section: Safety and Medicinal Use Related To Fungal And Plant Colourantsmentioning
confidence: 99%